Exploring the Intersections of Artificial Intelligence, Organizational Behavior, and Communication Dynamics in the Modern Workplace - Ioseb Gabelaia; Ramunė Bagočiūnaitė; Viktorija Navickienė (International School for Social and Business Studies, 2024)
Purpose: While organisations struggle to improve efficiency and productivity, the interaction between AI, organisational behaviour, and communication dynamics tends to be complex in the rapidly evolving modern workplace. Moreover, understanding the implications of this intersection is necessary to encourage a balanced and effective workplace. Hence, employing AI technologies in organisational structures introduces challenges such as workforce adaptation, psychological impact, and communication patterns. This research explored how AI influences organisational behaviour and communication dynamics in the modern workplace. Study design/methodology/approach: This study used a mixed method to explore organisational behaviour and communication dynamics across diverse industries comprehensively. This questionnaire aimed to gather respondents' experiences, focusing on organisational behaviour and communication dynamics. Furthermore, in-depth interviews were conducted with key stakeholders (n = 13) to obtain additional insights into goodness and trustworthiness. These interviews offered more depth and richness, providing insights into organisational settings. This mixed methodology ensured a complex understanding of the research problem, leveraging quantitative and qualitative data to enhance the analysis. Findings: The research findings revealed the pathways to how AI influences organisational behaviour and communication dynamics. Initial analysis of survey data and interviews offered insights into employee perceptions, identifying potential challenges and opportunities. One major trait emerging from data analysis is employees' unstable levels of apprehension and enthusiasm regarding AI integration. While many view it as a mechanism for efficiency, productivity, and innovation, others indicate distress about job shifts and loss of autonomy. Understanding and adopting these opposing insights are fundamental for encouraging a positive organisational ecosystem for AI readiness and adoption. Originality/value: By examining the impact of AI on employees' attitudes, collaboration, and communication patterns, this research contributes viable insights for organisations navigating the integration of AI into their structures.